Anti-inflammatory and toxicity studies of atranorin extracted from Cladina kalbii Ahti in rodents (Brazilian Journal of Pharmaceutical Sciences, 2011)
Atranorin (ATR) is the main compound from the lichen Cladina kalbii Ahti, which grows in the arid regions of northeastern Brazil. This study was conducted to evaluate the anti-inflammatory and toxicological properties of ATR. To evaluate anti-inflammatory properties, paw edema was induced by injecting 0.1 mL of carrageenan into the subplantar region of the right hind paw of rats, and leukocyte migration was induced by injection of 500 µL of carrageenan into the peritoneal cavity of mice. In addition, we determined ATR cytotoxicity in L929 cells by MTT assay and acute (5 g/kg-single dose) and subchronic (50 mg/kg-30 days) toxicity tests in Wistar rats. The results showed that ATR (100 mg/kg and 200 mg/kg) exhibited significant anti-inflammatory activity (paw edema and leukocyte migration). In the acute toxicity test, the animals showed hypoactivity and lethargy during the initial period (first 6 hours) and increase in total protein, total and indirect bilirubin, and alkaline phosphatase after 14 days in ATR-treated male rats. The subchronic toxicity test revealed increases in total protein, globulin, gamma-glutamyl transferase, alkaline phosphatase, and total and direct bilirubin in ATR-treated female rats. Histological analysis revealed no changes in the architecture and morphology of the organs. These results suggest that ATR has significant anti-inflammatory activity, with no significant acute and subchronic toxicity or cytotoxicity.